2022
DOI: 10.3389/fpsyg.2022.808192
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Edged Impact of Social Smartphone Use on Smartphone Addiction: A Parallel Mediation Model

Abstract: Evidence supports predictive roles of non-social smartphone use for smartphone addiction, but the relationship of social smartphone use and smartphone addiction is unclear. This study explored whether social smartphone use has a double-edged impact on smartphone addiction. Using data from a sample of 909 Chinese undergraduates, we tested a parallel mediation model that considered online social support and realistic social support as mediators. As predicted, social smartphone use weakened smartphone addiction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…It is also expected that respondents with high social engagement playfulness more frequently use Facebook and LINE, i.e., social smartphone use. Previous studies reported a positive relationship between social smartphone use and smartphone dependency because in social smartphone use, people can make new friends without in-person communication, which can decrease social anxiety, enhance social comfort, and easily increase their number of friends, and this notion supports the finding of the current study [ 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is also expected that respondents with high social engagement playfulness more frequently use Facebook and LINE, i.e., social smartphone use. Previous studies reported a positive relationship between social smartphone use and smartphone dependency because in social smartphone use, people can make new friends without in-person communication, which can decrease social anxiety, enhance social comfort, and easily increase their number of friends, and this notion supports the finding of the current study [ 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…The effect of agreeableness on ARA behavior in social networking (H2) was rejected in this study. Individuals who agree easily tend to have empathy in their real-world friendships (Chang et al, 2022;Getzmann et al, 2021;Jeon et al, 2018). Agreeable individuals also have good personal relationships in social networks, as well as in real life (Chang et al, 2022).…”
Section: The Influence Of Agreeableness On Ar Face Filter Addiction O...mentioning
confidence: 99%
“…Individuals who agree easily tend to have empathy in their real-world friendships (Chang et al, 2022;Getzmann et al, 2021;Jeon et al, 2018). Agreeable individuals also have good personal relationships in social networks, as well as in real life (Chang et al, 2022). Therefore, the individual does not consider social networking as the only way to fulfill one's social needs (Chang et al, 2022).…”
Section: The Influence Of Agreeableness On Ar Face Filter Addiction O...mentioning
confidence: 99%
See 2 more Smart Citations